(untitled) (Journal of Sciences & Technology, 2018)
Heat transfer process and fluid flow in a Solar Chimney Power Plant System (SCPPS) are investigated numerically. As simulation object we use the Spanish prototype plant. The calculative model and boundary conditions in calculation are introduced. Boussinesq model was chosen in the natural convection processus, Discrete Ordinate radiation model was employed for radiation. The principal factors that influence on the performance of the Solar Chimney have been analysed. The effects on the flow of the Solar Chimney which caused by solar radiation intensity have been simulated. The calculated results are compared and are approximately equivalent to the relative experimental data of the Manzanares prototype. It can be concluded that the temperature difference between the inlet and outlet of collector, as well as the air velocity in the collector of the system, is increase with the increase of solar radiation intensity and the pressure throughout system is negative value.